Acosmism and Passage to the Finite: Hegel as a Reader of Spinoza: Hegel Leitor de Spinoza - Lanciote, Diego (Revista Eletrônica Estudos Hegelianos, 2024)
This work investigates two interconnected issues. The first involves an analysis of Hegel's reading of the notions of substance, attribute, and mode in Spinoza, highlighting how Hegel characterizes this philosophy as acosmitic in contrast to the notion of pantheism. Furthermore, it explores the reasons why Hegel associates Spinoza's philosophy with Eleaticism, resulting in the thesis of the "immobility of substance," which is contrasted with Hegel's own project, centered on the thesis of the "becoming-Subject of substance." From this context rooted in Hegel's interpretation of Spinoza, the second issue addressed is the passage from the infinite to the finite, which is a translation of the effectivation of infinite substance into its finite modes. This problem is investigated in relation to the broader context of German Idealism, emphasizing Spinoza's crucial role in the construction of Hegel's philosophical project. In this context, the epistolary debate between Schelling and Fichte involving Spinoza is analyzed to gain a clearer understanding of the inversion of quantity into quality in Hegelian perspective.
Keywords: Acosmism; finitude; infinitude; quality; quantity